A novel fusiform aneurysmal model in a rabbit carotid: a combination of pericarotid calcium chloride and elastase incubation. (3rd June 2015) - Alaqeel, A; Meek, C; Wong, J; Mitha, A
Abstract : Background: The purpose of this study was to develop a novel, simple and effective model of fusiform artery aneurysms in rabbits using a combination of periaortic calcium chloride (CaCl2) and elastase incubation. Methods: Fusiform aneurysms were developed in three New Zealand White rabbits by exposing a 2 cm segment of the right carotid artery to CaCl2 (0.5 mol/L) and pancreatic porcine elastase (75 U) for 20 minutes. The left carotid was used as a control. Vessel diameter was measured by serial digital subtraction angiography imaging at weeks 2, 4 and 6. Animals were sacrificed on week 6 and histopathological studies were performed. Results: All rabbits developed a fusiform aneurysm, with an average dilation ratio of 105%±10% by week 6. No mortality was reported. Histopathological studies revealed pathological features consistent with fusiform aneurysms. Conclusions: This novel rabbit model of fusiform carotid aneurysms is the first in the literature by using a combination of periaortic CaCl2 and elastase incubation. This is a simple, reliable, and effective technique and results in a potentially valuable model for the study of fusiform aneurysms and possible therapeutic interventions, such as flow diversion.